Overview of current software capabilities for EEG recording and analyzing - A. A. Ivanov (Эпилепсия и пароксизмальные состояния, 2023)
This article is aimed at familiarizing medical specialists involved in the registration and analysis of electroencephalographic (EEG) examinations with the basic principles of work and the capabilities of current computer software for EEG recording and analyzing. Understanding the basics of how the software works should help medical staff use all its functionality correctly and ultimately improve the quality of medical care. The basic and innovative capabilities of computer software in the field of mathematical processing and analysis of EEG signals are discussed, the limitations of using mathematical processing methods are described.